ALEKSANDR MAKEDONISKIYNING HARBIY YURISHLARI - Nazarova Gulshan Xaydar qizi, Panjiyeva Mavjuda Ozod qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, Alexander's campaigns in his youth, the reforms he carried out in the territory of the country. The conquest of the great Achaemenid Empire by Alexander the Great is reported.